Staff Studies for the World Econ Outlook, August 1987. (World Economic and Financial Surveys; World Economic and Financial Surveys, 1987)
This paper reviews the long-term growth performance of the major industrial countries and discusses some of the many factors that have been identified as possible sources of the marked slowdown in growth since the early 1970s. According to the view of different demographic developments across countries, it is useful to break the growth of output down into changes in tabor input and changes in labor productivity in order to obtain a basis for cross-country comparisons. Wage behavior in the face of energy price shocks appears to have differed considerably among the major industrial countries. Increased uncertainty, reflecting, in particular, changes in the international economic environment and the stop-go financial policies of several of the major countries during the 1970s, and is frequently cited as a possible reason for the slowdown in growth, mainly through its impact on private investment. Views on the contribution of slower net capital accumulation to the deceleration in growth depend upon assessments of whether the efficiency of investment declined significantly after 1973 and on assumptions made about technological change and the embodiment of technical progress.